Postoperative serum squamous cell carcinoma antigen and carcinoembryonic antigen predict overall survival in surgical patients with esophageal squamous cell carcinoma - Huang, Yi; Liu, Fangfang; Xu, Ruiping; Zhou, Fuyou; Yang, Wenlei; He, Yu; Liu, Zhen; Hou, Bolin; Liang, Linlin; Zhang, Lixin; Liu, Mengfei; Pan, Yaqi; et al. (Frontiers in Oncology, 2023)
Background Tumor markers are routinely used in clinical practice. However, for resectable patients with esophageal squamous cell carcinoma (ESCC), they are applied infrequently as their prognostic significance is incompletely understood. Methods This historical cohort study included 2769 patients with resected ESCC from 2011 to 2018 in a high-risk area in northern China. Their clinical data were extracted from the Electronic Medical Record. Survival analysis of eight common tumor markers was performed with multivariable Cox proportional hazards regressions. Results With a median follow-up of 39.5 months, 901 deaths occurred. Among the eight target markers, elevated postoperative serum SCC (Squamous cell carcinoma antigen) and CEA (Carcinoembryonic antigen) predicted poor overall survival (SCC HRadjusted: 2.67, 95% CI: 1.70-4.17; CEA HRadjusted: 2.36, 95% CI: 1.14-4.86). In contrast, preoperative levels were not significantly associated with survival. Stratified analysis also demonstrated poorer survival in seropositive groups of postoperative SCC and CEA within each TNM stage. The above associations were generally robust using different quantiles of concentrations above the upper limit of the clinical normal range as alternative cutoffs. Regarding temporal trends of serum levels, SCC and CEA were similar. Their concentrations fell rapidly after surgery and thereafter remained relatively stable. Conclusion Postoperative serum SCC and CEA levels predict the overall survival of ESCC surgical patients. More importance should be attached to the use of these markers in clinical applications.